Find the derivatives of the following functions with respect to x.
𝑥3 + 𝑦3 = 3
𝑦 = (sin 𝑥)𝑡𝑎𝑛𝑥
ANSWER
a) If "{ x }^{ 3 }+{ y }^{ 3 }=3" , then "y(x)={ { \\left( 3-{ x }^{ 3 } \\right) }^{ \\frac { 1 }{ 3 } }=f(g(x)) }.\\ g(x)=3-{ x }^{ 3 }\\ ,\\ f(x)={ x }^{ 1\/3 }" . By the Chain Rule, we have "y'(x)=f'(g(x))\\cdot g'(x)" . "g'(x)=-3{ x }^{ 2 }\\quad ,\\ f'(x)=\\frac { 1 }{ 3 } { x }^{ -\\frac { 2 }{ 3 } }" . Hence
"y'(x)=-\\frac { 1 }{ 3 } { \\left( 3-{ x }^{ 3 } \\right) }^{ -\\frac { 2 }{ 3 } }\\cdot 3{ x }^{ 2 }=-{ \\left( 3-{ x }^{ 3 } \\right) }^{ -\\frac { 2 }{ 3 } }\\cdot \\ { x }^{ 2 }" .
b) Since "{ a }^{ b }={ e }^{ b\\ lna }\\quad (a>0)" , then "y(x)={ { e }^{ (\\tan { x } )\\cdot \\ln { (\\sin { x) } } \\quad } }".So, by the Chain Rule:
"y'(x)={ e }^{ (\\tan { x } )\\cdot \\ln { (\\sin { x) } } \\ }\\left[ (\\tan { x } )\\cdot \\ln { (\\sin { x) } } \\right] '."
"\\left[ (\\tan { x } )\\cdot \\ln { (\\sin { x) } } \\right] '="
"={ (\\sec { x) } }^{ 2 }\\cdot \\ln { (\\sin { x) } } +(\\tan { x } )\\cdot \\left[ \\ \\frac { \\cos { x } }{ \\sin { x } } \\right] ="
"= { (\\sec { x) } }^{ 2 }\\cdot \\ln { (\\sin { x) } } +1." Therefore,
"\\quad y'(x)=({ \\sin { x) } }^{ \\tan { x } }\\cdot \\left[ { (\\sec { x) } }^{ 2 }\\cdot \\ln { (\\sin { x) } } +1 \\right]"
Comments
Leave a comment